2015
DOI: 10.1159/000430250
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Administration of Glutamate Triggers a Non-Apoptotic, Autophagic Response in PC12 Cells

Abstract: Background/Aims: Increasing amounts of the neurotransmitter glutamate are associated with excitotoxicity, a phenomenon related both to homeostatic processes and neurodegenerative diseases such as multiple sclerosis. Methods: PC12 cells (rat pheochromocytoma) were treated with various concentrations of the non-essential amino acid glutamate for 0.5-24 hours. The effect of glutamate on cell morphology was monitored with electron microscopy and haematoxylin-eosin staining. Cell survival was calculated with the MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Mitogen-activated protein kinases (MAPKs) are a family of proteins involved in a wide range of cell responses mediated by inflammatory stimuli and previous works observed that RAGE activation leads to fast cell responses involving MAPK signaling cascade [28-32]. Thus, we analyzed the effect of eHSP70 on the activation state of the MAPKs ERK1/2, p38 and JNK.…”
Section: Resultsmentioning
confidence: 99%
“…Mitogen-activated protein kinases (MAPKs) are a family of proteins involved in a wide range of cell responses mediated by inflammatory stimuli and previous works observed that RAGE activation leads to fast cell responses involving MAPK signaling cascade [28-32]. Thus, we analyzed the effect of eHSP70 on the activation state of the MAPKs ERK1/2, p38 and JNK.…”
Section: Resultsmentioning
confidence: 99%
“…Because this concentration of glutamate does not induce toxicity and cell death, it is conceivable that the induced autophagy is related to the physiological function of this neurotransmitter [37]. …”
Section: Discussionmentioning
confidence: 99%
“…This indicates that physiological and stimulatory conditions lead to autophagy induction, which may act selectively to remove damaged organelles in a cytoprotective process [36, 37]. Glutamate is also a metabolic substrate, and particularly in astrocytes it exerts a critical role in energy production, by recycling the excessive glutamate released in synaptic cleft and converting to α-ketoglutarate and ammonia [38] therefore, in both neurons and glia, it is a source of energy, which is important for the storage of neurotransmitters as well as brain function [35].…”
Section: Discussionmentioning
confidence: 99%
“…Cytosolic Ca 2+ is a potent activator of autophagy, and several excitotoxic neurotransmitters — including glutamate, N -methyl-D-aspartate (NMDA) and kainic acid — induce the expression of autophagy biomarkers in the rodent brain, possibly as a compensatory response to damage 62,63 . The depletion of BECN1 by siRNAs as well as pharmacological inhibitors of autophagy aggravated (whereas rapamycin and trehalose limited) the demise of primary rodent neurons and multiple neuronal cell lines of human origin that were exposed to glutamate, NMDA or kainic acid in vitro 64,65 , which suggests that autophagy supports neuronal viability in the course of excitotoxic challenges.…”
Section: Autophagy As a Therapeutic Targetmentioning
confidence: 99%